Exploring the causal relationship between CX3CL1 and prostate cancer prognosis using Mendelian randomization - Weisheng Li; Baoguo Xia; Weixin Chu; Likui Lu; Xuedong Liu (Discover Oncology)
Abstract Background Prostate cancer (PCa) is a common cancer in men, making up about 21% of male cancer cases worldwide. Although prostate cancer is common, little is known about its causes, which makes treatment more difficult. Studies suggest that immunity and inflammation are linked to prostate cancer. This study explores whether inflammatory mediators play a role in its development and outcome. Methods Single-nucleotide polymorphisms (SNPs) associated with CX3CL1 expression (GWAS ID: ebi-a-GCST90012074) were identified from a genome-wide association study (GWAS) of 21,758 individuals of European descent. Summary-level data from three PCa GWAS datasets were obtained from the UK Biobank: ieu-b-4809 (9,132 cases and 173,493 controls), ukb-b-1392 (7,847 cases and 455,163 controls), and ukb-d-C3_PROSTATE (6,321 cases and 354,873 controls). Mendelian randomization (MR) was first used to assess the causal relationship between CX3CL1 and PCa. A meta-analysis was then conducted to evaluate the overall genetically predicted risk. Finally, the impact of CX3CL1 on PCa was further explored using gene expression data, immune cell infiltration profiles, survival analysis, and single-cell sequencing. Results Two-sample Mendelian randomization analysis indicated that CX3CL1 was inversely associated with PCa risk. The subsequent meta-analysis supported a consistent inverse causal relationship between CX3CL1 levels and PCa risk. Further analysis showed that CX3CL1 expression was significantly downregulated in tumor tissues compared with normal tissues, and was positively correlated with immune cell infiltration. Lower CX3CL1 expression was also associated with poorer prognosis in PCa patients. In addition, single-cell sequencing revealed that CX3CL1 expression was markedly reduced in cancer cells compared with other cell populations within the tumor microenvironment. Conclusion This study demonstrated that genetically predicted CX3CL1 levels are inversely associated with PCa risk. Further analysis using public databases showed that reduced CX3CL1 expression in PCa cells is associated with lower immune cell infiltration, which may contribute to poorer prognosis. These findings suggest that CX3CL1 may serve as a potential biomarker for predicting PCa risk and patient outcomes and that immunotherapy strategies targeting CX3CL1 could offer therapeutic benefits for PCa patients.